Proteins at the tRNA Binding Sites of Escherichia coli Ribosomes - Czernilofsky, Armin P. (1974)
p - Nitrophenylcarbamyl - phenylalanyl-tRNA binds to ribosomes in response to poly(U) and reacts with ribosomal proteins via covalent bond formation. Ribosomal proteins of Escherichia coli were characterized by two-dimensional gel electrophoresis and by reaction with specific antibodies. The affinity label is shown to react with the 50S proteins L27, L15, L2, L16, and L14. We therefore conclude that these particular proteins are located at or near tRNA-binding sites within the 50S ribosomal subunit.